The Effect of Income, Education, Literacy and Religiosity on the Amount of Cash Waqf Among the Millenial Generation - Surantino, Rayyan; Sri Muljaningsih (Islamic Economics and finance in Focus, 2025)
Indonesia holds vast potential for cash waqf development; however, only 1.28% of this potential has been realized. Understanding the factors that drive cash waqf contributions is therefore essential. This study aims to examine the influence of income, education, literacy, and religiosity on the amount of cash waqf among the millennial generation in Java Island. The research adopts a quantitative approach, with data collected through questionnaires distributed via Google Forms. Respondents were required to be Muslim, part of the millennial generation, residing in Java Island, and having experience in making cash waqf. Data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings reveal that income, education, and religiosity significantly influence the amount of cash waqf among millennials in Java Island, while literacy does not show a significant effect.